Response to Frederic Bretzner et al. “Target Populations for First-In-Human Embryonic Stem Cell Research in Spinal Cord Injury” - Wirth, Edward; Lebkowski, Jane S.; Lebacqz, Karen (Cell stem cell, 2011)
We address concerns raised in this issue by Bretzner et al. (2011) by explaining the rationale for including subjects with subacute, neurologically complete spinal cord injuries in the Phase 1 trial of GRNOPC1. We also present elements of the informed consent process that minimize the likelihood of therapeutic misconception.